SNP_TATA_COMPARATOR: Web SERVICE FOR COMPARISON OF SNPs WITHIN GENE PROMOTЕRS ASSOCIATED WITH HUMAN DISEASES USING THE EQUILIBRIUM EQUATION OF THE TBP/TATA COMPLEX - D. A. Rasskazov; K. V. Gunbin; P. M. Ponomarenko; O. V. Vishnevsky; M. P. Ponomarenko; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
Web-service SNP_TATA_Comparator has been developed for using experimentally proven in silico evaluation of in vivo biochemical manifestations of SNPs in the core promoter regions of human genes associated with diseases on the base of the TBP/TATA complex equilibrium equation (TBP is TATA binding protein). Data of individual deviations from the reference human genome (Ensembl, rel. 68, i.e. the variant of human genome commonly accepted as datum in comparison analysis) are accessible for free in the real-time mode. Also, data from the GENCODE database (rel. 17) are automatically invoked. The reported Web service SNP_TATA_Comparator is designed for personalized medicine using individual genomes in diagnosis, monitoring, prevention, and treatment.